Short term load forecasting based on Internet of Things (IoT) - Uz Zaman, Mahdi; Islam, Anisul; Sultana, Nahid (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.